Fostering Organizational Citizenship Behavior: Job Characteristics and Employee Engagement Among PPSU Workers - Suyani Maryam; Alfatih Manggabarani; Tri Siswantini; Rosali Sembiring Colia (Sean Institute, 2026)
This study examines the impact of job characteristics and employee engagement on Organizational Citizenship Behavior (OCB) among frontline public service workers in Indonesia, specifically within the Public Infrastructure and Facilities Maintenance Unit (PPSU), referred to as the “Orange Troops.” We used a quantitative explanatory research design to get data from 96 PPSU employees using a structured questionnaire. Job characteristics were assessed utilizing the Job Characteristics Model, employee engagement was evaluated through the Utrecht Work Engagement Scale, and Organizational Citizenship Behavior (OCB) was quantified using recognized multidimensional frameworks. We used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data. The results show that both job characteristics (β = 0.430, p < 0.001) and employee engagement (β = 0.305, p = 0.001) positively and significantly affect OCB. The model explains 43% of the variance in OCB (R² = 0.43), indicating a moderate level of predictive power. These findings suggest that employees are more likely to exhibit discretionary, prosocial behaviors when their jobs are meaningful, autonomous, and well-structured, and when they feel engaged and committed to their work. This research enhances the public sector organizational behavior literature by emphasizing the essential functions of job characteristics and engagement in promoting organizational citizenship behavior among urban service employees. In practice, companies can improve OCB by making jobs more compelling and keeping employees engaged through initiatives that recognize, support, and help them grow.